ІЗОТЕРМІЧНИЙ ПЕРЕРІЗ ДІАГРАМИ СТАНУ СИСТЕМИ CeО2–La2O3–Eu2O3 ПРИ ТЕМПЕРАТУРІ 1250 C - Kornienko , Oksana; Bykov, Oleksandr; Sameliuk, Аnatoliy; Yurchenko, Yuri (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2020)
Using the methods of physicochemical analysis (XRD, petrography, scanning electron microscopy analyses) phase equilibria were firstly investigated in the ternary system СeO2–La2O3–Eu2O3 system at 1250 ºС. It was established that in the system there exist fields of solid solutions based on cubic with fluorite-type structure (F) and cubic (С) and monoclinic (B) modification Eu2O3 and hexagonal (A) modification of La2O3. No new phases were found. The refined lattice parameters of the unit cells for solid solutions for the systems were determined. The cubic ceria-based solid solution has a ﬂuorite-type structure and homogeneity ﬁeld shows the maximum extension. It forms solid solutions of substitution type with phases of binary systems. The boundary of the homogeneity ﬁeld of F-phase is curved from the center of triangle toward the CeO2 corner and passes through appropriate points in the binary CeО2-Eu2O3(100-69 mol % CeO2) and CeO2–La2O3 (100-51 mol% CeO2) systems. The lattice parameters for F phase vary from а = 0.5409 nm in pure СеО2toа = 0.5512 nm in two-phase sample (F + C) containing 55 mol % CeО2-22.5 mol % La2O3-22.5 mol % Eu2O3and to а = 0.5526 nm in three-phase sample (F + В + C) containing 40 mol % CeО2-30 mol % La2O3-30 mol % Eu2O3 and to а = 0.5532 nm in three-phase sample (А + F + В) containing 30 mol % CeО2-35 mol % La2O3-35 mol % Eu2O3along the section CeO2 ( 50 mol % La2O3-35 mol % Eu2O3). The lattice parameters for F phase vary from а = 0.5409 nm in pure СеО2 to а = 0.5444 nm nm in two-phase sample (F + C), containing 70 mol % CeО2-3 mol % La2O3-27 mol % Eu2O3and to а = 0.5465 nm in three-phase sample (F + В + C) containing 20 mol % CeО2-8 mol % La2O3-72 mol % Eu2O3. The homogeneity field of solid solution based on A-La2O3 extends to 17 mol % СеO2 and 20 mol % Eu2O3 in the corresponding binary systems and locates near the composition 5 mol % CeO2-90 mol % La2O3-5 mol % Eu2O3 on the section La2О3 - (50 mol % CeО2-50 mol % Eu2О3). The boundary of the homogeneity ﬁeld of B- Eu2O3 phase passes through appropriate points in the binary CeО2-EuO3 (0-1 mol% CeO2) and–Eu2O3 (0-25 mol% La2O3) systems. The isothermal section of the CeO2– La2O3–Eu2O3 system at 1250°C contains four three-phase regions (A+F+B, F+B+C) and five two-phase regions (F+A, A+B, F+B, B+C, F+C).